Vibrational and Compositional Analysis Associated with the Color of Guadua angustifolia Kunth Variety Bicolor (GAKVB) - J. I. Cárdenas; C. Vargas-Hernandez (Advances in Materials Science and Engineering)
The vibrational modes and compositional behavior of plant material of Guadua angustifolia Kunth Variety Bicolor (GAKVB) and the characteristics associated with color changes were evaluated by Raman, infrared, and energy-dispersive X-ray spectroscopy. In the vibrational spectra, the frequencies of 1598, 2099, and 845 cm−1 were associated with yellow and blue pigments. These pigments can be found in natural organic dyes of vegetable origin, such as indigo blue (anil or pastel), extracted from Central American shrubs (Indigofera and indaco) (Domenech, 2010), in some pigments synthesized in solid-state reactions from aluminum oxides, such as CaAl12O19, that have a turquoise color (Costa et al., 2009), and in Indian yellow (MgC19H16O11·5H2O). Using an immersion test, it was shown that the color was stable and that no loss of color occurred when photosynthesis was halted in the sample. The green and yellow stripes are assigned to Fe, N, Mg, and Si compounds. The yellow is due to decrease of Fe, Mg, and elemental Si. Results are obtained using energy-dispersive X-ray spectroscopy and Raman measurements.